Financial management in construction contracting - Ross, Andrew, 1960-; Williams, Peter (Chichester, West Sussex : Wiley-Blackwell, 2013)
'This textbook provides a general introduction to costing and budgeting for construction but in particular it covers CVRs. There is a wide range of approaches to preparing these reports and, without being over-prescriptive, the authors provide a useful framework for students by giving an outline of the key requirements, together with an evaluation of the alternatives'--
Includes bibliographical references and index.
Keywords: Construction industry -- Accounting; Construction industry -- Finance